Evaluation of effectiveness of breaking fragments passing performed by rally crews - Olga Kuvaldina (Kharkiv State Academy of Physical Culture, 2015)
Purpose: to develop a methodology and criteria for evaluating the effectiveness of braking fragments performed by rally crews. Material and Methods: using the method of video shooting at 60 film/sec, we recorded the kinematic characteristics of passing a braking fragment with length of 90 m performed by 38 rally crews of different skill level, all of them are participants of the 4th cycle of the Rally Cup of Ukraine 2014. Results: we have found defining, as for fragment passing time, characteristics for different groups of crews according to a position at the definite cycle, a position at the Cup testing, sporting improvement stages and vehicle classes. Conclusions: speed deviations at entering the braking fragment, maximum, and exit out of the braking fragment and their total deviations from benchmark indices shown by winners of the competition are realizable efficiency criteria of braking fragments performed by rally crews